Bandung dan Pemaknaan Dago dalam Sejarah: Masa Lalu, Masa Kini - Frans Ari Prasetyo (Universitas Gadjah Mada, 2019)
This article explores the history of Bandung, in particular the Dago street area, as a history of place. It looks into how Bandung include Dago has been defined, its etymology and the way in which the people that inhabit the place use and place meaning to these urban spaces. The article argues that civic meaning is rooted in the historic creation of place. It also looks into civic design and civic reform going through different governmentality from the colonial up into the present period to see how much the meaning of place is both historical but also politic and strategic to the present needs of the people that inhabit it.